Downward Propagating Equatorial Kelvin Wave over the Eastern Indian Ocean as Revealed from Radiosonde and GPS Radio Occultation (CHAMP) Data - Noersomadi Noersomadi; Tri Wahyu Hadi (Jurnal Matematika & Sains, 2010)
Vertical propagation of equatorial Kelvin wave and its correlation with convective activity over the eastern Indian Ocean were investigated through analyses and inter-comparisons of radiosonde and GPS/CHAMP occultation data. The radiosonde data from 80 balloon launchings were obtained in the period of August 5 to 14, 2005 over the region of 1.640 N - 6.20 S, 88.20 E- 97.340 E surrounding the cruise track of R/V Mirai during Tropical Ocean and Climate Study (TOCS) campaigned. Results of radiosonde data analyses show a variation in the height of cold point tropopause (CPT) associated with Kelvin wave activities. In addition, coexisting strong convective activities were also detected during August 9 to 11, 2005.Â  The characteristics of equatorial Kelvin wave were further investigated by fitting a sinusoidal approximation by assuming zonal wave number 1 and 2 to the GPS/CHAMP temperature perturbations using non linear inversion algorithm. It is found that the periodicity of observed Kelvin wave is about 5 - 6 days. Inter-comparisons of low-pass filtered of height-time cross section of perturbation temperature from both radiosonde and GPS/CHAMP data showed downward propagation Kelvin wave, which was more pronounced during August 11 to 14, 2005. Furthermore, an increase in the potential and kinetic energy of the downward propagating Kelvin wave was observed prior to the occurrence of strong convection, which is believed as convectively coupled equatorial Kelvin wave.